KKN TEMATIK: KEGIATAN DALAM MEMBANGUN DESA TEMATIK BARUA BANTAENG: KKN TEMATIK: KEGIATAN DALAM MEMBANGUN DESA TEMATIK BARUA BANTAENG - adabi, adabi_darban; Hilmi Hambali; Muhammad Wajdi (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2024)
Thematic Real Work Lectures (KKNT) are a form of education by providing learning experiences to students for life in the community outside campus, which automatically together with the community identifies potential and handles problems so that it is hoped that they will be able to develop village/regional potential and create solutions for problems in the village. The implementation of an independent campus is carried out by studying outside the campus (university). Learning carried out in the community environment is carried out using a transdisciplinary approach, where this approach is one of the UM curriculum approaches, apart from the capability approach and life-based learning. The location of this KKNT activity is in Berua village, Ermerasa District, Bantaeng Regency, South Sulawesi Province. The learning carried out for KKNT students is Making Family Name Plates in each Berua Village community, then Revitalizing the Berua Village Office, then Stunting Socialization targeting students in Berua Village, Public Speaking and Leadership Training targeted at village communities, then cleaning The target environment is increasing community awareness of the importance of environmental cleanliness, then making village structure boards and village maps, then village profiles depicted on the village office walls, then teaching and learning activities targeted at schools and finally a competition targeted at community awareness of the importance of togetherness.